APLIKASI SHORT MESSAGE SERVICE (SMS) MENDUKUNG KEPATUHAN ANTIRETROVIRAL THERAPY (ART) ODHA - Yowel Kambu (Politeknik Kesehatan Kemenkes Sorong, 2020)
ABSTRACTThe most frequent nursing issues occured on People Living with HIV/AIDS (PLHA) are both risk ofinfections and lack of knowledge about treatment of medication. Nursing intervention based on evidencebased nursing inovation is using aplication of mobile phone of short message service (SMS) to monitoringand promote the client’s ART adherence ABSTRAKMasalah keperawatan terbanyak pada Orang hidup Dengan HIV/AIDS (ODHA) adalah risiko infeksidan kurang pengetahuan tentang regimen pengobatan. Inovasi intervensi keperawatan berbasis pembuktianadalah aplikasi short message services (sms) untuk memonitor dan mendukung kepatuhan terapiantireroviral.